Experimental zinc stress on benthic diatoms assemblage growth in Fyrisån water - Naghavian, Navid (2012)
Benthic diatoms are unicellular, brown algae with siliceous cell walls. They are often used to show water quality in river sand lakes. Benthic diatoms can show elevated nutrient levels, very acid conditions, pollution by organic matter and probably also pollution by heavy metals, which makes them useful biological indicator species. Observed impact of metal pollution on benthic diatoms are reductions in cell number, valve malformation and reduction of some diatom taxa which leads to a change in community structure. The present study is focusing on the impact of the heavy metal zinc. In aquatic environments, zinc exists in form of divalent cation Zn2+, hydrated zinc (pH=4-7) and moderately weak complexes. At higher pH (7-10) Zn2+ is replaced by adsorbed Zinc (ZnFe(OH)3), or aqueous ZnCO3and Zn(OH)2.. Zinc release to soil and aquatic environments may be from mining, smelting metals, steel production, waste incineration, burning coal and fossil fuel. Two hypotheses were tested in laboratory experiments in the present project: 1. The culture of benthic diatoms is possible under the given laboratory (artificial) conditions. 2. High concentrations of zinc (300μg/l zinc) decrease the number of benthic diatoms and increase abnormalities in cell walls. The first hypothesis “The culture of benthic diatoms is possible under the given laboratory (artificial) conditions.” was confirmed. Diatom cell numbers increased during the course of the first experiment. The second hypothesis that “High concentrations of zinc (300μg/l zinc) decrease the number of benthic diatoms and increase abnormalities in cell walls.” was not confirmed by this experiment, possibly due to the loss of the toxic zinc form from solution over time.